PENGARUH PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA BANK YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2015-2017) - ., Ani Karoma; ., Made Arie Wahyuni, S.E., M.Si.; ., Made Aristia Prayudi, S.A., M.Sc., Ak. (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2017)
Abstrak Penelitian ini bertujuan untuk menganalisa pengaruh Pengungkapan akuntansi sumber daya manusia dan pengungkapan CSR terhadap kinerja keuangan perusahaan.Penelitian ini merupakan penelitian kuantitatif.populasi dalam penelitian ini adalah seluruh perusahaan perbankan yang terdaftar dalam Bursa Efek Indonesia selama periode 2015-2017.Teknik pengambilan sampel dilakukan dalam metode purposive samplingdengan jumlah sampel yangdigunakan sebanyak 10 perusahaan perbankan yang listing di BEI periode 2015-2017. Data yang digunakan adalah data sekunder dengan menganalisis annual report perusahan. Metode analisis data menggunakan analisis regresi linier berbantuan SPSS versi.19 .Hasil penelitian menunjukkan bahwa 1) Pengungkapan akuntansi sumber daya manusia berpengaruh terhadap kinerja keuangan perusahaan.2)Pengungkapan Corporate Sosial Responsibility (CSR) berpengaruh terhadap kinerja keuangan perusahaan. 3) Pengungkapan akuntansi sumber daya manusia dan pengungkapan Corporate Sosial Responsibility (CSR) berpengaruh terhadap kinerja keuangan perusahaan Kata Kunci :Akuntansi SDM, CSR, ROA Abstract This study aims to analyze the effect of disclosure of financial resources and CSR disclosure on company financial performance. The study is quantitative research. The population in this study is the entire banking company listed in the Indonesia Stock Exchange during the period 2015-2017. The sampling technique is done by purposive sampling with the number of samples used is as many as 10 banking companies listing on the IDX in the period 2015-2017. The data used is secondary data by analyzing the company's annual report. The data analysis method uses multiple linear regression analysis. The results of the study show that 1) Disclosure of accounting resources is influenced by the performance of the company's earnings. 2) The disclosure of Corporate Social Responsibility (CSR) has an effect on the performance of the company's finances. 3) Disclosure of financial resources and disclosure of Corporate Social Responsibility (CSR) influences on the performance of the company's expenses Keywords: HR Accounting, CSR, ROA Abstrak Penelitian ini bertujuan untuk menganalisa pengaruh Pengungkapan akuntansi sumber daya manusia dan pengungkapan CSR terhadap kinerja keuangan perusahaan.Penelitian ini merupakan penelitian kuantitatif.populasi dalam penelitian ini adalah seluruh perusahaan perbankan yang terdaftar dalam Bursa Efek Indonesia selama periode 2015-2017.Teknik pengambilan sampel dilakukan dalam metode purposive samplingdengan jumlah sampel yangdigunakan sebanyak 10 perusahaan perbankan yang listing di BEI periode 2015-2017. Data yang digunakan adalah data sekunder dengan menganalisis annual report perusahan. Metode analisis data menggunakan analisis regresi linier berbantuan SPSS versi.19 .Hasil penelitian menunjukkan bahwa 1) Pengungkapan akuntansi sumber daya manusia berpengaruh terhadap kinerja keuangan perusahaan.2)Pengungkapan Corporate Sosial Responsibility (CSR) berpengaruh terhadap kinerja keuangan perusahaan. 3) Pengungkapan akuntansi sumber daya manusia dan pengungkapan Corporate Sosial Responsibility (CSR) berpengaruh terhadap kinerja keuangan perusahaan Kata Kunci :Akuntansi SDM, CSR, ROA Abstract This study aims to analyze the effect of disclosure of financial resources and CSR disclosure on company financial performance. The study is quantitative research. The population in this study is the entire banking company listed in the Indonesia Stock Exchange during the period 2015-2017. The sampling technique is done by purposive sampling with the number of samples used is as many as 10 banking companies listing on the IDX in the period 2015-2017. The data used is secondary data by analyzing the company's annual report. The data analysis method uses multiple linear regression analysis. The results of the study show that 1) Disclosure of accounting resources is influenced by the performance of the company's earnings. 2) The disclosure of Corporate Social Responsibility (CSR) has an effect on the performance of the company's finances. 3) Disclosure of financial resources and disclosure of Corporate Social Responsibility (CSR) influences on the performance of the company's expenses Keywords: HR Accounting, CSR, ROA keyword : This study aimed at analysing the impact of the disclosure of human resource accounting and corporate social responsibility on companies? financial performance. This study was a quantitative study. The population in this study were all banking companies registered at Indonesia Stock Exchange in 2015 until 2017. The samples were 10 banking companies registered at Indonesia Stock Exchange in the period 2015-2017, selected by applying pusposive sampling technique. The data used were secondary data by analysing the companies? annual reports. The method af data analysis applied was linear regression analysis assisted by SPSS version 19. The results of the analysis indicated that 1) human resource accounting disclosure had impact on companies? financial performance, 2) Corporate Social Responsibility (CSR) disclosure had impact on companies? financial performance, 3) human resource accounting and Corporate Social Responsibility (CSR) disclosures had impact on companies? financial performance.